Danos morais nos vícios de qualidade e quantidade por inadequação: análise da jurisprudência do Superior Tribunal de Justiça = Moral damages in quality and quantity deficiencies due to inadequacy: analysis of Brazilian Superior Court of Justice case law - Hirata, Alessandro (2020)
Submitted by betanial@stj.jus.br (betanial@stj.jus.br) on 2020-05-11T19:23:40Z No. of bitstreams: 2 danos_morais_vicios_hirata.pdf: 4070861 bytes, checksum: 8ada1531741b703bb79445e5e2954de9 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)